Accidental allergic reactions to food in adolescents and adults: An overview of the factors involved and implications for prevention - Versluis, Astrid; Le, Thuy-My; Houben, Geert F.; Knulst, André C.; Van Os-Medendorp, Harmieke (Frontiers in Allergy, 2023)
Accidental allergic reactions to food are one of the major problems in adult patients diagnosed with food allergy. Such reactions occur frequently, are often severe and are associated with higher medical and non-medical costs. The aim of this Perspective is to provide insight into the different factors involved in the occurrence of accidental allergic reactions and to present an overview of practical implications for effective preventive measures. Several factors affect the occurrence of accidental reactions. These factors are related to the patient, health care, or food. The most important patient-related factors are age, social barriers to disclosing their allergy and non-adherence to the elimination diet. With regards to healthcare, the degree to which clinical practice is tailored to the individual patient is an important factor. The major food-related factor is the absence of adequate precautionary allergen labeling (PAL) guidelines. Since many factors are involved in accidental allergic reactions, different preventive strategies are needed. It is highly recommended that health care be tailored to the individual patient, with regard to education about the elimination diet, support on behavioral and psychosocial aspects, usage of shared decision-making and taking into account health literacy. In addition, it is crucial that steps are taken to improve policies and guidelines for PAL.